Anti-Ri-associated paraneoplastic ophthalmoplegia-ataxia syndrome in a woman with breast cancer: a case report and review of the literature - Giuseppe Sena; Gaetano Gallo; Giuseppina Vescio; Denise Gambardella; Stefano de Franciscis; Mariuccia Renne (Journal of Medical Case Reports, 2020)
Abstract Background Breast cancer is the most common cancer in women. However, in the management of breast cancer, paraneoplastic neurological syndromes represent a diagnostic and therapeutic challenge. The diagnosis of paraneoplastic neurological syndromes is difficult due to the heterogeneity of symptoms, the timing of presentation, and the absence of antibodies, and it generally occurs before the diagnosis of breast cancer in 80% of patients who develop paraneoplastic neurological syndromes. We describe a 72-year-old woman with subacute ophthalmoplegia-ataxia syndrome who was subsequently diagnosed as having breast cancer and anti-Ri antibodies. Case presentation A 72-year-old post-menopausal Caucasian woman, with a positive medical history for diabetes mellitus and hypertension, presented with a 3-month onset of blurred vision, diplopia, and progressive gait disturbance. Serological tests were positive for well-characterized onconeural antibodies (anti-Ri). A whole-body computed tomography scan revealed a nodular opacity under her left nipple and axillary adenopathy. A biopsy of her left breast was performed, and histological examination showed ductal carcinoma. She underwent a superoexternal quadrantectomy with left axillary dissection. The final diagnosis showed infiltrating ductal carcinoma of the breast (T1c N1 M0, stage IIA) associated with paraneoplastic ophthalmoplegia-ataxia syndrome. At a 6-month follow-up, she showed no clinical or instrumental evidence of neoplastic recurrence with partial clinical improvement of neurological symptoms, such as ataxia and diplopia. Conclusion The diagnosis of paraneoplastic neurological syndromes is often late, as in this patient, but treatment at an early stage may provide a good prognosis. Furthermore, this is one of several cases of an anti-Ri paraneoplastic neurological syndrome not associated with myoclonus, which reinforces the belief that opsoclonus myoclonus syndrome is not pathognomonic of the associated anti-Ri paraneoplastic neurological syndromes.